Early years education teachers' perceptions of nature of science - Schofield, L; Takriti, R; Rabbani, L; AlAmirah, I; Ioannidou, O; Alhosani, N; Elhoweris, H; Erduran, S (Taylor and Francis, 2023)
Research indicates that teachers lack a sophisticated understanding of Nature of Science (NOS), which in turn, can impact their instructional decisions and students’ understanding of NOS. The aim of the study was to investigate United Arab Emirates (UAE) early years’ science teacher’s (N = 433) perceptions about the NOS. Results obtained from a 70-item questionnaire revealed that teachers have an adequate understanding on many aspects related to science and NOS, especially those pertaining to the ‘Social-Institutional’, ‘Scientific Practices’ and ‘Educational Applications’ categories. However, varied perceptions were found on some key concepts such as the role of bias and prejudices on scientiﬁc facts, the employment of same scientific practices across diﬀerent branches of science, and the influence of politics in science. Misconceptions on particular aspects of NOS were also recognised (e.g. the distinction between laws and theories and the fixed nature of procedures followed in experiments). The findings suggest practical and pedagogical implications for teaching and outline an agenda for further research.